A descriptive study of financial wellness influencing factors among Malaysian : Examining the moderating effect of personality - Wan Nor Fatihah Wan Hanafi (2015)
This project paper attempts to identify two factors influencing financial wellness among Malaysian people, which are Literacy and Social Status with the effect of personality factor as an enhancement. The aims of this study are to determine the influence factors of financial wellness among Malaysian, to examine the response towards financial wellness in terms of demographic profile, and finally to identify the moderating effect of personality between literacy and social status towards financial wellness.